ZILLENIAL MICROGENERATION: HYBRID TRAITS, DIGITAL BEHAVIOR, AND GENERATIONAL BOUNDARIES - Marielle Carganilla; John Rey Pelila (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
This narrative review explores the emerging concept of Zillennials, a microgeneration situated between Millennials and Generation Z, by synthesizing existing literature on their defining traits, values, and sociocultural behaviors. The study aims to clarify the characteristics that distinguish Zillennials from their parent generations, addressing the ambiguity surrounding generational boundaries. Using Google Scholar as the primary database, 434 initial sources were screened, resulting in 22 relevant studies. Text Data Mining and thematic analysis were employed to extract recurring themes and construct a coherent generational profile. Findings reveal that Zillennials exhibit hybrid traits, such as being digitally fluent yet cautious adopters of new technologies, valuing work-life balance and flexible arrangements, and demonstrating strong social awareness and ethical consumer behavior. Their communication style favors structured feedback and digital interaction, while their learning preferences lean toward independent, tech-supported methods. As a generational bridge, Zillennials blend the pragmatism of Millennials with the innovation of Gen Z, making them uniquely positioned to mediate cultural and technological shifts. By synthesizing fragmented insights across disciplines, this study provides a consolidated generational profile that advances our understanding of microgenerational identity and its implications. The study concludes that Zillennials should be recognized as a distinct cohort in educational, organizational, and societal contexts. Future researchers are recommended to explore their experiences across diverse settings and examine their responses to rapid digital and economic changes